2001
DOI: 10.1089/105072501753271734
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-Like Growth Factor Type 1, Insulin-Like Growth Factor-Binding Protein-1, and Insulin-Like Growth Factor-Binding Protein-3 Concentrations in Patients with Thyroid Dysfunction

Abstract: Thyroid hormones play a role in the regulation of insulin-like growth factor type 1 (IGF-1) and insulin-like growth factor-binding protein-3 (IGFBP-3) expression, and both IGF-1 and IGFBPs have been shown to be related to the function and growth of the thyroid. Our aim was to evaluate serum concentrations of IGF-1, IGFBP-1, and IGFBP-3 in patients with thyroid dysfunction before and after normalization of thyroid function. The study was performed in 86 patients with thyroid dysfunction (43 hyperthyroid and 43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 32 publications
1
37
1
2
Order By: Relevance
“…Insulin-like growth factor I levels are low in adults with hypothyroidism and may normalize after thyroid hormone replacement therapy [3,28]. In hyperthyroidism, IGF-I levels have been shown to be normal or elevated and to decrease following antithyroid treatment with either total thyroidectomy or methimazole [3].…”
Section: Thyroid and Adrenal Diseasementioning
confidence: 99%
“…Insulin-like growth factor I levels are low in adults with hypothyroidism and may normalize after thyroid hormone replacement therapy [3,28]. In hyperthyroidism, IGF-I levels have been shown to be normal or elevated and to decrease following antithyroid treatment with either total thyroidectomy or methimazole [3].…”
Section: Thyroid and Adrenal Diseasementioning
confidence: 99%
“…Previous studies reported discrepant results regarding circulating IGF1 levels: lower, 8,9 unmodified 10,11 or even higher values [12][13][14] in hyperthyroid compared to euthyroid patients. These discrepant results may be due to different laboratory tests used, changes in the number of IGF1R, 21,22 an interaction between the anabolic effect of IGF-related peptides and the catabolic thyrotoxic condition 16 or changes associated with nutritional signals and/or energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…9 Iglesias et al demonstrated in 2001 that hypothyroidism is associated with significant reductions of IGF1 and IGFBP3 and that IGFBP1 is elevated in both hypothyroidism and hyperthyroidism. 10 Co ng et al showed, in a study performed on adolescent hyperthyroid patients, that hyperthyroidism does not cause alterations in the serum concentrations of either free or total IGF1. In the same study, both serum IGFBP2 and IGFBP3 concentrations were elevated during hyperthyroidism and correlated with serum T4 levels.…”
Section: Introductionmentioning
confidence: 98%
“…This may be a limitation of our study. Although the relationships between thyroid hormones and GH/IGFs axis are complex and not fully understood, results of clinical investigations generally suggest that there is a decrease in IGF-1 and IGFBP-3 in patients with hypothyroidism and that these molecules significantly increase following L-T 4 replacement therapy [21][22][23][24][25][26][27]. Due to the existence of strong correlations between age and IGF-1/ IGFBP-3 [28], the continuity of relationships between IGF-1/IGFBP-3 and thyroid hormones (T 3 , fT 4 ) after adjustment for age is in agreement with previous studies that suggest close relationships between GH/IGF axis and thyroid functions [2,21,23].…”
Section: Discussionmentioning
confidence: 99%